Fabrication of In2O3 doped PbO2 anode and its application for electrochemical degradation of norfloxacin in aqueous solutions. Issue 6 (December 2021) - Wang, Qian; Tu, Shiqi; Wang, Weiyi; Liu, Liyue; Duan, Xiaoyue; Chang, Limin
Abstract: To improve the electrochemical activity and stability of PbO2 electrode, In2 O3 particles were doped into β-PbO2 active layer by composite electrodeposition technology. When the In2 O3 concentration in electrodeposition solution was 2 mM, the In2 O3 -PbO2 electrode had larger specific surface area, tighter crystal structure, higher oxygen evolution potential (2.09 V vs. SCE), smaller charge transfer resistance (64.32 Ω/cm 2 ), stronger ability to generate hydroxyl radicals (0.213 μM/min) and thereby the better electrocatalytic activity and stability. In electrochemical oxidation of norfloxacin (NOR), the NOR removal rate at the In2 O3 -PbO2 anode was 1.388 times faster than that at pristine PbO2 electrode. Additionally, the effects of current density, initial pH, initial NOR concentration and electrolyte concentration on NOR removal efficiency were investigated by the principle of single variable. With the increase of current density and the decrease of initial NOR concentration, the NOR removal efficiency increased significantly; the better degradation effect was obtained under pH 3 and Na2 SO4 concentration of 0.2 M. Finally, the degradation mechanism of NOR was discussed and five possible degradation pathways were proposed. Graphical Abstract: ga1 Highlights: Doping In2 O3 particles greatly improved the electrochemical activity of PbO2 anode. Tafel curve was adopted to evaluate the stability of Ti/In-PbO2 electrode. Chronoamperometry was performed to study electrochemical oxidation of norfloxacin. The electrochemical degradation mechanism of norfloxacin was proposed.